(untitled) (Research, Society and Development, 2024)
Introduction: Sexually Transmitted Infections in pregnant women harm pregnancy due to vertical transmission, which causes increased morbidity and mortality for the pregnant woman and the baby. STIs in pregnant women can cause miscarriage, prematurity, low birth weight, sepsis, blindness, pneumonia and congenital deformities. Objectives: To carry out a literature review on the epidemiology of STIs in pregnant women in Brazil, aiming at reducing STI cases and protecting the fetus from the numerous possible consequences resulting from vertical transmission. Methodology: The study was carried out through a Integrative literature review, with emphasis on scientific articles published in the databases Analysis of Medical Literature and Online Retrieval System (MEDLINE), Latin American and Caribbean Literature in Health Sciences (LILACS) and the Nursing Database (BDENF). The descriptors used in the research were: (“IST” and “pregnancy” and “vertical transmission”). Results: When analyzing the selected articles, it was found that there were flaws in prenatal care related to the prevention of syphilis and other STIs during pregnancy, in addition to the non-use of condoms, which demonstrated the importance of early diagnosis and treatment, thus aiming at a reduction of the rates of vertical transmission. Conclusion: The importance of addressing issues related to the influence of the correct treatment of pregnant women with STIs on the prognosis of the newborn is evident, since these infections negatively affect pregnant women, fetal development and post-birth.